Carl J. Mora: Classic Mexican Cinema Online. From the Achives of the Filmoteca of the Universidad Nacional Autónoma de México (BRILL. P.O Box 2000-2300 PA Leider, The Netherlands - González Zúñiga, Julián (2017)
Historia del cine mexicano y sus etapas.